The science of rural human settlements: a comprehensive overview - Liu, Junyou; Zheng, Bohong; Tang, Haifang (Frontiers in Environmental Science, 2023)
In the process of rapid urbanization in the world, many villages are facing a series of problems such as depopulation, population agingageing, insufficientimperfect infrastructure, and public service facilities. In order for better rural development and full implementation of the 2030 sustainable development goals, we should hammer at improving the rural human settlement. Based on the science of human settlement proposed by Constantinos Doxiadis, biliometric analysis was made on studies related to rural human settlement in the last 25 years. Through analysis, we believe that the number of related studies will gradually increase. Currently, the improvement of the rural ecological environment and the creation of a healthy rural human settlement environment are two hot topics. It is very likely that these topics will also be highly focused in the following decades. With the gradual development of rural areas and the improvement of the material lives of people, more and more scholars will pay attention to higher-level demands such as rural cultural environment and self-realization of villagers. By building the evaluation index system reviewing literatures related to rural human settlement, we can comprehensively consider different aspects to look at the problems in rural human settlement from different side.This kind of research is quite beneficial for the comprehensive development of rural human settlement. Scholars in different countries have similar focuses related to rural human settlement. However, because of different country conditions, the foucusesfocuses of researchers have some obvious differences. Scholars from different countries did research on rural human settlement as a part of the science of human settlement so that related scholars around the world could strive to improve rural human settlement under the same discipline background. Relevant literature contributes to the development of the science of human settlement.